Epidemiologic Profile of Patients With Epilepsy in a Region of Southeast Brazil: Data From a Referral Center - Buainain, Renata Parissi; Oliveira, Carlos Tadeu Parisi; Marson, Fernando Augusto Lima; Ortega, Manoela Marques (Frontiers in Neurology, 2022)
Introduction Epilepsy affects about 50 million people worldwide, 80% of whom live in low- and middle-income countries. In Brazil, epidemiological studies are outdated and restricted to specific regions, mostly due to the continental size of country. Objective We aimed to present the first evidence-based study on the epidemiological aspects of individuals with epilepsy, mapping the characteristics of this disease in a referral center in a region of Southeast Brazil. Methods A retrospective study was carried out from January 2010 to March 2021. Patients were selected according to the International League Against Epilepsy Criteria. Results From a total of 618 selected patients, 317 (51.3%) were men and 301 (48.7%) were women with an average age of 34.03 ± 20.66 years. The average age at the first seizure was 15.16 ± 17.61 years. The prevalence ratio was 1.30 cases/1,000 habitants. Childhood febrile seizure was present in 44 patients (7.9%) and family history of epilepsy in 231 (37.4%) patients. The predominant type of seizure was focal in 401 (64.9%) patients. The most frequent etiologies were structural in 254 (41.1%) patients and unknown in 238 (38.5%) patients. Most of the patients' treatments were based on anti-seizure drugs in monotherapy [389 (62.9%)] with 398 (64.4%) drug-responsive patients. Conclusions Our epilepsy prevalence rate was lower than other studies in the Southeast Region of Brazil. In addition, the structural epilepsy type was predominant in our study compared with unknown causes, which is more frequent in other Brazilian regions and worldwide studies. The differences may be attributed to our region, which presents a high prevalence of neuroinfection, specially neurocysticercosis, and a referral center for traumatic brain injury. Moreover, the contrasting results reinforce the need for an adequate epidemiological assessment of epilepsy incidence in a region of Southeast Brazil.